The Dynamics of Infall and Accretion Shocks in the Outer Disk - Susan Terebey; Loraine Sandoval Ascencio; Lizxandra Flores-Rivera; Neal J. Turner; Andrew Barajas (The Astrophysical Journal)
High-spatial-resolution observations of disks around young stars suggest planetary systems begin forming early, during the protostellar phase (≤1 Myr) when stars accrete most of their mass via infall from the surrounding cloud. During this era, shocks are expected to be ubiquitous around the gaseous accretion disk, due to supersonic infall that strikes the disk. We investigate the role of shocks using a theoretical and modeling framework we call the shock twist-angle Keplerian (STAK) disk, connecting the disk and infalling envelope gas via a shock using general physical principles. Briefly, at the shock, energy is dissipated while angular momentum is conserved, so that the infalling gas must change direction sharply, yielding a bend or twist in the streamlines. The model’s pre-shock gas follows freefall parabolic trajectories, while the post-shock gas is on lower-energy, elliptical orbits. We construct synthetic observations and find that the deviations from circular Keplerian orbits are detectable in Doppler-shifted molecular spectral lines using radio interferometers such as ALMA. Specifically, the STAK model leads to line emission intensity and velocity-moment maps that are asymmetric and offset with respect to the disk structure traced by the dust continuum. We examine archival ALMA data for the class 0/I protostar L1527 and find the C ^18 O velocity moment map has features resembling the disk-plus-envelope emissions that naturally arise when the two are connected by a shock. Thus, spectral line observations having sub-km s ^−1 spectral resolution and angular resolution sufficient to fully resolve the disk can reveal protostars’ envelope-disk shocks.